Positional body composition of female division i collegiate volleyball players - Bisch, K. L.; Bosch, T. A.; Carbuhn, A.; Stanforth, P. R.; Oliver, J. M.; Bach, C. W.; Dengel, D. R. (The Journal of Strength and Conditioning Research, 2020)
The primary study objective was to measure positional differences in total and regional body composition among female NCAA Division I collegiate volleyball players using dual X-ray absorptiometry (DXA). The secondary objective was to examine normative age curves for fat and lean mass (LM) variables. Ninety female volleyball players from 5 universities received a DXA scan. Athletes were categorized by position: middle blocker (MB = 31), outside hitter (OH = 32), setter (ST = 9), and Libero (LB = 18). Height, body mass, total and regional fat mass (FM), LM, bone mineral density (BMD), and abdominal visceral adipose tissue were measured by DXA. Body mass distribution ratios were calculated. The secondary age analysis included a subset of 153 DXA scans (n = 83, ages 18-21 years). Front row players (i.e., MB and OH) had significantly greater total and regional LM and BMD measures (p < 0.05, all), compared with non-front row players (i.e., LB and ST). Differences in total LM (p < 0.001) were significantly influenced by height. Front row players had consistently lower mass distribution ratios compared with non-front row players (p < 0.05, all). Lean mass index (LMI, p = 0.752) and FM index (FMI, p = 0.392) were not significantly different across ages. Back row players have greater relative upper body mass, whereas mass in front row players is more evenly distributed between the upper and lower body. Bone mineral density differences may be influenced by repeated impact of jumping during the attacking and blocking actions of front row players. Minimal changes in LMI and fluctuations in FMI can be expected across an athlete's career.